Pengaruh Kompetisi dan Kerjasama Terhadap Kinerja Individu dengan Iklim Kepedulian Sebagai Variabel Mediasi Serta Informasi Kinerja Relatif Sebagai Variabel Moderasi. - Yudi Hartono; Monika Palupi M (ITB AAS INDONESIA, 2023)
This study aims to measure the effect of cooperation and competition on individual performance through a caring climate as a mediating variable and relative performance information as a moderating variable. The research was carried out with the quantitative methods and data was collected directly using a scale measurement survey to the research partisipants. The results of the regression analysis on this study show the empirical evidence that the cooperation and competition assignments can have a direct effect on performance. Meanwhile the caring climate variable can’t mediate the effect of competition and cooperation model to the individual performance. In the other hand, relative performance information can has a significant influence on the relationship between caring climate and performance. Keywords: Cooperation and competition ; Caring climate ; Performance .